Contraceptive method use trajectories among young women in Kenya: A qualitative study - Calhoun, Lisa M.; Mandal, Mahua; Onyango, Bernard; Waga, Erick; McGuire, Courtney; Zulu, Eliya M.; van den Akker, Thomas; Benova, Lenka; Delvaux, Thérèse; Speizer, Ilene S. (Frontiers in Global Women's Health, 2022)
Background Many young women experience important key life transitions during adolescence and early adulthood, such as initiation of sexual activity, first use of contraceptives, marriage and childbirth. For young women to be able to plan and manage their lives, it is critical to understand how these life events intersect and shape their contraceptive decision-making. This study aims to explore young women’s contraceptive method use trajectories, including the factors that influence contraceptive decision-making throughout adolescence and youth. Methodology In 2019, the Full Access, Full Choice project (FAFC), implemented by the University of North Carolina at Chapel Hill and the African Institute for Development Policy, conducted 30 in-depth interviews with young women aged 18-24 years in three counties in Kenya (Nairobi, Mombasa and Migori). Eligible respondents had used two or more modern contraceptive methods. Interview guides utilized a modified life history approach to capture details about respondents’ contraceptive use and life experiences from the time they first used contraception until the time of interview. Results We identified five separate contraceptive use trajectories based on the occurrence and timing of marriage, childbirth, and contraceptive method choice as well as various influences on contraceptive decision-making. The majority of respondents began their contraceptive journey by using male condoms or emergency contraception, but subsequent contraceptive decisions were varied across trajectories and influenced by different factors. For many women, the initiation of a non-coitally dependent method occurred after the birth of a child; for some, this was the first method used. Once women transitioned to using a non-coitally dependent method such as injectables or implants, many cycled through different methods to find one that had fewer side effects or provided the desired duration of protection. Discussion This study highlights the nuanced needs of young women throughout their adolescent and youth years in Kenya. This suggests that programs and policies need to encompass young women’s diversity of experiences and motivations to best serve them.